From online platforms to digital monopolies : technology, information and power - Valente, Jonas Chagas Lúcio (Studies in critical social sciences, 2021)
"In From Online Platforms to Digital Monopolies: Technology, Information and Power Jonas C.L. Valente discusses the rise of platforms as key players in different social activities, from economy to culture and politics. These companies have a daily presence in the lives of the majority of the world population, from social interactions to digital payments and transactions. They are gaining a central role in neoliberal capitalism, shaping contemporary sociability. The book shows how these platforms work and identifies the hidden interests behind the commercial strategies that guide the development of services offered to Internet users. It takes the specific cases of Google and Facebook and presents its historical development, illustrating how these companies turned into major players in our times"--